1966
DOI: 10.1002/jsfa.2740170301
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of eggs

Abstract: Published work on the chemical composition of eggs, with particular reference to the protein and lipid constituents, is reviewed and summarised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
4

Year Published

1970
1970
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 92 publications
2
40
0
4
Order By: Relevance
“…Egg whites consisted of 85 g/100 g water, 10 g/100 g protein, and 5 g/100 g other components such as lipid, carbohydrate, and ash (Stadelman & Cotterill, 1977). The protein compositions in egg whites are 54 g/100 g ovalbumin, 13 g/100 g conalbumin, 11 g/100 g ovomucoid, and 22 g/100 g others (Parkinson, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…Egg whites consisted of 85 g/100 g water, 10 g/100 g protein, and 5 g/100 g other components such as lipid, carbohydrate, and ash (Stadelman & Cotterill, 1977). The protein compositions in egg whites are 54 g/100 g ovalbumin, 13 g/100 g conalbumin, 11 g/100 g ovomucoid, and 22 g/100 g others (Parkinson, 1966).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it has been suggested that LOX1 had a greater affinity for charged substrates and a lower affinity for neutral ones, regardless of the pH of the solution (24), and interacted with monomeric substrate rather than with fatty acid inserted into detergent micelles. However, the results obtained in this study clearly show that LOX1 had a greater affinity for the fatty acid inserted into the PDM-micelles than for the monomeric substrate.…”
Section: Effect Of Ph and Ionic Strength On The Ph Activity Profilementioning
confidence: 99%
“…Yolk lipid thus exists associating with protein as lipoprotein. 16) IgY is one of the live tins (y-livetin). Therefore, removal of the lipoprotein (or lipid) is an important step for the purification ofIgY.…”
Section: Discussionmentioning
confidence: 99%